TA’WIL AYAT-AYAT KAUNIYAH PERSPEKTIF REVOLUSI INDUSTRI 4.0 DAN REVOLUSI SOSIAL 5.0 - Sholatiah, Yessi Sundari, Rahmad Affandi Nst, Harun Al Rasyid (CV. Adiba Aisha Amira, 2024)
This research examines and analyzes kauniyah verses which are often recited in accordance with currently developing scientific theories, namely the development of industrial revolution 4.0 and social revolution 5.0. The focus of this research is more on the relevance of the kauniyah verses which are often recited in accordance with the development of science in the era of revolution 4.0 and 5.0 with the presence of scientific cues in each kauniyah verse which then becomes a guide in today’s modern research. This research uses qualitative research, based on library research. In a previous study from Wirdawati et al, they proved in their research that the Al-Qur’an is related to science. The findings in this study concluded that 1). The Al-Qur'an has clearly mentioned kauniyah verses which contain studies related to the development of science and technology in the industrial revolution 4.0 and social revolution 5.0. 2). There is a very strong relevance in the Kauniyah verses which always invite us to think through the universe so that we can carry out research and find new findings that continue to develop.